Multivariate Statistics and Typology: Consuming Aesthetic Services in Brazil (Global Journal of Management and Business Research, 2014)
The main goal of this study was to understand the ways in which a particular group perceives the body and the decisions for its modification through body aesthetics services. A total of 215 undergraduate students of a Brazilian public university were interviewed (Federal University of Mato Grosso do Sul). Open-ended questions made it possible to know the main representations of the female body, the ways of perceiving the body. Definitions of ugly body and beautiful body explained the group's relationships with the size of their own bodies, the dilemmas regarding the current beauty standards, the difficulty in feeling satisfied, and the search for aesthetic services with the aim of transforming their social identity. The adoption of multivariate statistical techniques enabled the presentation of the proposed typology. The results of this study are intended to contribute to marketing studies, attributing significant importance to the consideration of the cultural dimension in studies on consumption behavior.
Keywords: marketing; consumer behavior; social representations; multivariate statistics; lexical analysis